Tailoring the selectivity in 2-butene conversion over supported d0 group 4, 5 and 6 metal hydrides: from dimerization to metathesis1. Issue 10 (21st October 2015) - Szeto, Kai C.; Merle, Nicolas; Rios, Cesar; Rouge, Pascal; Castelbou, Jessica Llop; Taoufik, Mostafa
<x xml:space="preserve">Abstract</x> 2-Butenes are transformed in a continuous flow reactor over metal hydrides of zirconium, tantalum and tungsten supported on silica–alumina. Exceptionally high selectivity to dimeric products is obtained over supported zirconium hydride catalysts.